2010
DOI: 10.1242/dev.047332
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of pre- and postsynaptic neurons via nephrin/NEPH1 homologs is a basis for the formation of theDrosophilaretinotopic map

Abstract: SUMMARYTopographic maps, which maintain the spatial order of neurons in the order of their axonal connections, are found in many parts of the nervous system. Here, we focus on the communication between retinal axons and their postsynaptic partners, lamina neurons, in the first ganglion of the Drosophila visual system, as a model for the formation of topographic maps. Post-mitotic lamina precursor cells differentiate upon receiving Hedgehog signals delivered through newly arriving retinal axons and, before matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 53 publications
1
50
0
Order By: Relevance
“…Although the exact function of Neph1 at the podocyte cell membrane is unclear, its role in the podocyte development is supported from the studies with Drosophila and Caenorhabditis elegans models in which it has been shown to be involved in axonal guidance and synapse development, respectively (58,59). Since Myo1c also localizes to the actin-rich periphery and plasma membrane and has been shown to be involved in regulating dynamic cellular processes, including vesicle trafficking, cell migration, cell spreading, and membrane tension (15,23,27,55,60), it is likely that the interaction between Neph1 and Myo1c contributes toward the regulation of Neph1 signaling and trafficking.…”
Section: Fig 10mentioning
confidence: 99%
“…Although the exact function of Neph1 at the podocyte cell membrane is unclear, its role in the podocyte development is supported from the studies with Drosophila and Caenorhabditis elegans models in which it has been shown to be involved in axonal guidance and synapse development, respectively (58,59). Since Myo1c also localizes to the actin-rich periphery and plasma membrane and has been shown to be involved in regulating dynamic cellular processes, including vesicle trafficking, cell migration, cell spreading, and membrane tension (15,23,27,55,60), it is likely that the interaction between Neph1 and Myo1c contributes toward the regulation of Neph1 signaling and trafficking.…”
Section: Fig 10mentioning
confidence: 99%
“…The expression of nephrin in neuronal cells is of particular interest because the nephrin orthologues in Caenorhabditis elegans (Syg-2) and Drosophila melanogaster (Hibris) are crucial players in synapse targeting and positioning (45,46), suggesting that, evolutionarily speaking, the original function of nephrin is that of a synaptic adhesion molecule.…”
Section: Essential Role Of Nephrinmentioning
confidence: 99%
“…1Ruiz-Gómez et al (2000), Strünkelnberg et al (2001).2Komori et al (2008).3Strünkelnberg et al (2001).4Sugie et al (2010).5Bour et al (2000).6Artero et al (2001), Dworak et al (2001).7Shen and Bargmann (2003).8Shen et al (2004).9Dottermusch-Heidel et al (2012).10Prakash et al (2005).11Fannon and Colman (1996), Uchida et al (1996).12Bao et al (2007).13Najarro et al (2012).14Aravamudan et al (1999).15Maruyama and Brenner (1991).16Brose et al (1995).17Takamori et al (2006).18Estrada et al (2007).19Stevens et al (2012).20Nonet et al (1999).21Stenius et al (1995).22Jahn et al (1985).23Wiedenmann and Franke (1985).24Knaus et al (1990).25Hornbruch-Freitag et al (2011).26Perin et al (1991)27DiAntonio et al (1993).28Nonet et al (1993).…”
Section: Cellular and Molecular Biology Of Myoblast Fusionmentioning
confidence: 99%